The Effect Of Adding Cmc (Carboxymethyl Cellulose) To The Quality Of Purpel Sweet Potato Jam - Risandi, Lara; Holinesti, Rahmi; Faridah, Anni; Mustika, Sari (Universitas Negeri Padang, 2023)
Purple sweet potato (Ipomoea batatas L. Poir) is a vine that contains lots of anthocyanins and fiber, very beneficial for human health. Jam is a food product with a gel consistency so that the formation of gel in jam is highly desirable. The obstacle in making purple sweet potato jam is that the gel formation is not strong enough. So it is necessary to add food ingredients to form a gel, namely Carboxymethyl Cellulose (CMC). The addition of CMC aims to determine the effect of adding CMC on the quality of purple sweet potato jam with the effect of adding CMC of 0.5%, 1%, 1.5% and 2% on the quality of purple sweet potato jam from organoleptic tests. This research was conducted in January - February 2023 at tata boga workshop, Department of Family Welfare, Faculty of Hospitality Tourism, Universitas Negeri Padang. This type of research was a pure experiment using a completely randomized design (CRD) consisting of 5 treatments and 3 repetitions. To analyze the quality of the purple sweet potato jam, it was carried out through an organoleptic test involving 3 expert panelists. The data obtained is then tabulated and followed by statistical analysis (ANOVA), if Fcount ≥ Ftable then it will be continued with Duncan's test. The results showed that the addition of CMC had an effect on texture being soft and easy to spread, while the other indicators had no effect in terms of color, aroma and taste. The best research results of Carboxymethyl Cellulose (CMC) were found in treatment X4. The overall highest achievement score was color 3.67 (2%), aroma 3.89 (0%), soft texture 4.00 (2%), texture easily smeared 4.00 (2%), sweet taste 3.89 (2%) and purple sweet potato flavor 3.67 (2%). the addition of CMC had a significant effect between 0.5%, 1%, 1.5% and 2% on the quality of purple sweet potato jam, namely the quality of the soft texture and the texture easily smeared with purple sweet potato jam. The best quality test results for purple sweet potato jam with the addition of CMC were in treatment X2 with the addition of 2% CMC.